Caracterização do grau de desenvolvimento econômico e social dos municípios paranaenses : um estudo utilizando estatística multivariada - Rezende, Luiz Paulo Fontes de (2003)
The state of Paraná presented expressive transformation in the 90´s propitiated by productive and technological restructuring of productive sectors and by the decentralization of public politics. Such transformation not only made this state much more competitive, at the national and international levels, but also altered the spatial and sectorial structure on its economic activities. In such context of changes, the aim of this research was to characterize the development degree of 399 Parana´s districts through the factorial method analysis application. In order to obtain that, 35 referring variables to the social economical aspects of this state were used, which were reduced to 5 factors of development: F1 - industrial/commercial/services; F2 - urban/social; F3 - agricultural; F4 - educational and F5 - health. These factors are able to explain 83, 89% of the model total variance. The industrial commercial development and services (F1) of Paraná has a very unequal and concentrating profile, only Curitiba, Londrina and Maringá presented a very high development degree. It was also verified that the industrial development of Curitiba has a diversification degree superior to Londrina and Maringá, since the indexes differ highly. In relation to the development of the other factors, results did not show large discrepancies among the municipal districts, in spite of low development degree in some municipal districts. The results presented by these factors may also provide tools for regional planning and for orientation of investments.